Phytochemical Screening, Phenolic Content and Antioxidant Activity of Citrus aurantifolia L. Leaves Grown in Two Regions of Oman: Antioxidant activity and quantification of phenolics in Omani lime - Al Namani, Jokha; Baqir, Esra; Al Abri, Ajwaa; Al Hubaishi, Tamadher; Husain, Asif; Shah Alam Khan (Iranian Journal of Pharmaceutical Sciences, 2018)
Lime or Citrus aurantifolia L., is a small citrus fruit that belongs to the family Rutaceae. The fruit and leaves of C. aurantifolia have been used traditionally for weight loss, skin care, relief from constipation and treatment of scurvy, etc. The purpose of this study was to determine the flavonoid, total phenolic content, and investigation of anti-oxidant potential of Citrus aurantifolia leaves grown in Oman. Lime leaves were collected from Batinah (Nakhal) and Ad-dakhiliya (Nizwa) region of Oman. The leaves were dried, powdered, and extracted with ethanol using a hot extraction method. Standard chemical tests were used to check the presence of secondary plant metabolites in the lime leaves extract. Quantitative analysis of the phenolics and flavonoids were done by colorimeteric methods. The antioxidant activity was assessed by DPPH and phosphomolybdenum in vitro assay methods respectively. Chemical analysis of the lime leaves extract showed the presence of major secondary plant metabolites. The obtained results revealed variation in the content of flavonoid (41.38-64.2 μg of QE/mg of dry extract) and phenolic compounds (96.55-322.57 μg of GAE/mg of dry extract). Both the lime leaves extracts from Nakhal and Nizwa showed concentration dependent moderate anti-oxidant activity (11.79-56.89 and 10.11-51.91%). Lime leaves from Batinah region also exhibited better total antioxidant capacity calculated with reference to the standard gallic acid. The aerial part of C. aurantifolia seems to be a rich source of flavonoids. Further studies are recommended to isolate and quantify the pure phytoconstituents from lime leaves grown in the Batinah (Nakhal) region which might serve as natural antioxidants in food and drug industry.